Status and prospects for the use of diagnostic tools based on the method of gas-discharge visualization - Zinchenko, O.M.; Oliinyk, V.P.; Podpruzhnykov, P.M. (Radiotekhnika, 2024)
Diagnostic tools based on the gas-discharge visualization method were created for scientific and applied research of biological and non-biological objects, the state of the environment. The diagnostic essence of the method is the connection of the glow of an electric discharge around the object in the atmospheric air with the electrophysical properties of the internal and surface structures of the object, which in turn are interpreted as medical and biological indicators for living organisms, or technical characteristics for non-living ones structures. With the help of these tools, you can diagnose the human body, study liquids and materials of organic and inorganic origin. The disadvantages of the method include the dependence of informative indicators of discharge images not only on the properties of the object, but also on the constancy of the parameters of the surrounding environment. There are no uniform metrological requirements for the technical means of gas discharge visualization, which prevents their practical application. The purpose of the research is to find technical solutions for the construction of gas-discharge visualization tools to achieve the potential possibilities of their practical application. The analysis of the physical and technical conditions of gas-discharge visualization showed that with the relative constancy of the physical regularities of the discharge, the modes of measurement of the informative indicators of the images in these means differ significantly (amplitude, frequency, duration, form of alternating voltage). The known designs differ in the type of sensor, method and device of primary radiation registration, algorithms for reproduction and processing of the diagnostic image. It is proposed to standardize the technical characteristics of these tools and algorithms for obtaining informative indicators to compare correctly the diagnostic results obtained by different researchers (especially in the medical field). It is advisable to expand the use of gas-discharge visualization tools for controlling the composition of technical liquids, non-destructive flaw detection of materials and structures. It is recommended to add information about the characteristics of the surrounding atmospheric air (temperature, humidity, pressure) when conducting diagnostics.